Peran Orang Tua dalam Pendidikan Seksual Anak sebagai Upaya Mencegah Pernikahan Anak (Studi Kasus Di Desa Batujai Kabupaten Lombok Tengah - Mirah Diantari, Gusti Ayu Kade; Nugroho, Wahyu Budi; Kebayantini, Ni Luh Nyoman (JURNAL ILMIAH SOSIOLOGI: SOROT, 2022)
This study analyzes the role of parents in child sex education as an effort to prevent child marriage in Batujai Village, Central Lombok Regency. This study uses a qualitative approach with descriptive explanative type and analysis using the role theory of Biddle and Thomas. Through research that has been done, it is known that in practice what happened in Batujai Village that not all parents provide sex education to their children due to lack of understanding of parents to provide sex education to children. Parents who do not provide sex education hand over the responsibility for sex education to formal and informal educational institutions. As for parents who provide sexual education to children, it is carried out with preventive socialization methods, namely by giving advice or prohibitions to children and repressive socialization methods, namely by giving punishments, namely limiting children's association or confiscation of facilities provided to children. Keywords; roles, parents, sexual education, child marriage